Management of a non-vital immature tooth using MTA as an apical plug: Two case reports - Wagle, S; Joshi, N; Prajapati, K (Journal of Chitwan Medical College, 2015)
MTA appears to be a valid option for apexification with its main advantage being, the speed at which the treatment can be completed. A major problem in performing endodontics in immature teeth with necrotic pulp and wide open apices is obtaining an optimal seal of the root-canal system. Mineral Trioxide Aggregate (MTA), has been proposed as a potential material to create an apical plug at the end of the root-canal system, thus preventing the extrusion of filling materials. DOI: http://dx.doi.org/10.3126/jcmc.v5i1.12574